Comparison of rotary blade types on bulk density in puddled soil under varying conditions: Comparative analysis of rotary blades by RSM - Indraveer Sigh, Indraveer Sigh; Chaturvedi, Shalini; Kumar, Avinash; Shrivastava, Atul Kumar; Guru, Prabhat Kumar (ORYZA-An International Journal of Rice, 2025)
This study investigates the influence of rotary blade design, operational width and depth, rotary speed, and forward speed on soil bulk density during tillage/weeding operations. A comparative analysis was conducted on three rotary blade designs with different shapes (serrated, finger, and plain-shaped rotary blades) under varying field conditions of vertisol. The data were optimized using the Box-Behnken Design (BBD) within the framework of Response Surface Methodology (RSM). Data from all experimental setups revealed that the lowest soil bulk density (1.35 g cm-³) was achieved using serrated blades at a depth of 40 mm, width of 100 mm, forward speed of 1.50 km h-1, and rotary speed of 180 rpm. Among all configurations, the highest bulk density (1.59 g cm-³) was recorded for plain blades at approximately 60 mm depth and 106 mm width, with a forward speed of 1.80 km h-1 and rotary speed of 178.47 rpm. Finger blades showed optimal performance at lower depths (20 mm), achieving a bulk density of 1.48 g cm-³ at a rotary speed of 210 rpm. Notably, across all treatments, desirability values were consistently rated at 1.00, indicating high suitability of the tested conditions. The most desirable configuration involved serrated blades at a depth of 44 mm, width of 120.88 mm, forward speed of 1.52 km h-1, and rotary speed of 179.17 rpm, producing a bulk density of 1.37 g cm-³. Overall, serrated blades demonstrated superior effectiveness in soil pulverization compared to the other blade types. These findings highlight the potential of fine-tuning tillage parameters to optimize soil conditions and operational performance.